2019
DOI: 10.1111/cen.14111
|View full text |Cite
|
Sign up to set email alerts
|

Seated saline infusion test in predicting subtype diagnosis of primary aldosteronism

Abstract: Context:Although saline infusion test is widely used as a confirmatory test for primary aldosteronism (PA), it is reportedly less sensitive in patients in whom aldosterone is responsive to the upright position by performing it in recumbent position.Based on a single-centre experience, seated saline infusion test (SSIT) has been reported to be highly sensitive and superior to recumbent testing in identifying both unilateral and bilateral forms of PA. However, due to limited participants number, the utility of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Also, these three comparative studies were done in Asian populations with PA which can have differences in ion channel mutations and MC2R expression in the tumours. A recent study in a Japanese population found that PAC following seated saline infusion test is more predictive (sensitivity, 93.8%; specificity, 79.2%) for lateralization than PAC following ACTH stimulation test under dexamethasone suppression (sensitivity, 75.0%; specificity, 68.8%) . A previous study in a predominant Caucasian population did not report the cut‐off for maximal peripheral PAC following ACTH associated with 90% specificity to discriminate lateralized PA from nonlateralized PA …”
Section: Discussionmentioning
confidence: 94%
“…Also, these three comparative studies were done in Asian populations with PA which can have differences in ion channel mutations and MC2R expression in the tumours. A recent study in a Japanese population found that PAC following seated saline infusion test is more predictive (sensitivity, 93.8%; specificity, 79.2%) for lateralization than PAC following ACTH stimulation test under dexamethasone suppression (sensitivity, 75.0%; specificity, 68.8%) . A previous study in a predominant Caucasian population did not report the cut‐off for maximal peripheral PAC following ACTH associated with 90% specificity to discriminate lateralized PA from nonlateralized PA …”
Section: Discussionmentioning
confidence: 94%
“…All patients were diagnosed with PA according to the guidelines of the Japan Endocrine Society [ 13 ] and Japanese Society of Hypertension [ 14 ], including case detection and confirmatory tests. Case detection and confirmatory tests of PA and AVS were performed and evaluated as previously described [ 6 ]. Before the diagnosis, antihypertensive drugs were generally changed to calcium channel blockers and/or α-adrenergic blockers.…”
Section: Methodsmentioning
confidence: 99%
“…SSIT was performed as previously described in a hospitalized setting [ 6 ]. Briefly, patients remained in the sitting position during the transvenous infusion of 2 L of 0.9% saline, which contains 18 g sodium chloride, over 4 hours starting at 0900 am (Day 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reassessment of the cut-off values for confirmatory tests also brought an additional meaning in subsequent subtyping. With relatively small number of PA patients, a Japanese group revealed another aspect of SIT as a subtyping tool [ 137 ]. Based on the analysis of the receiver operating characteristic curve, they proposed an optimal cut-off value of PAC after seated saline infusion as 13.1 ng/dL for subtype prediction, which had a sensitivity of 0.94 and a specificity of 0.79 for unilateral PA [ 137 ].…”
Section: Recent Advance In Simplifying the Pa Diagnostic Flowmentioning
confidence: 99%